To 'Vape' or Smoke? A Discrete Choice Experiment among Adult Smokers - Joachim Marti; John Buckell; J. Catherine Maclean; Jody L. Sindelar (Institute of Labor Economics (IZA), 2017)
A growing share of the United States population uses e-cigarettes. In response, policymakers are considering regulating e-cigarettes, or have already done so, due to concerns regarding e-cigarettes' public health impact. However, there is currently little population-based evidence to inform these regulatory choices. More information is needed on how policy-relevant factors will likely drive smokers' decision to use e-cigarettes. To provide this information we conduct an online survey and discrete choice experiment to investigate how adult tobacco cigarette smokers' demand for cigarette type varies by four policy-relevant attributes: 1) whether e-cigarettes are considered healthier than tobacco cigarettes, 2) the effectiveness of e-cigarettes as a cessation device, 3) bans on use in public places such as bars and restaurants, and 4) price. Overall, we find that the demand for e-cigarettes is motivated more by smokers' health concerns than by the desire to avoid smoking bans or higher prices. However, results from latent class models reveal three distinct groups of smokers, those who prefer: tobacco cigarettes, e-cigarettes, and using both products. Each group responds differently to the cigarette attributes suggesting that policies will have different impacts across the groups.
Keywords: C35; I12; I18; 330; e-cigarettes; smoking; discrete choice experiments; preference heterogeneity; regulation